PENGARUH EKSTRAK ETANOL DAUN UBI JALAR UNGU (Ipomoea batatas L.) TERHADAP LEUKOSIT DAN LIMFOSIT MENCIT JANTAN BALB/C YANG DI INDUKSI VAKSIN HEPATITIS B - Siti Hamidatul Aliyah; Desi Sagita; Devi Kurnia (JURNAL BIOSENSE, 2021)
Abstract Background: Purple sweet potato leaves (Ipomoea batatas L.) which has been known as immunomodulatory activity, which contains chemical compounds, such as vitamins, minerals, flavonoids (anthocyanin), especially iron found in a higher proportion in the leaves. Therefore, it is necessary to study the immunomodulatory activity of the leaf extract of purple sweet potato (Ipomoea batatas L.) on the immune response in Balb/c mice who induced by hepatitis B vaccines. Method: Inducing performed at day 0 and day 15. Mice with weights ± 20 g, which has been divided into normal control group, I, II, III, IV and V (each 5 mice), respectively were given orally by the leaf extract of purple sweet potato (Ipomoea batatas L.) (doses 100 mg / kg, 200 mg / kg, 300 mg / kg, 400 mg / kg and 500 mg / kg), normal controls (CMC Na 0,5%). With the volume of giving 1% of body weight in mice, performed during the study (20th days). Blood sampling is done via the tail vein (laeralis vein), to calculate the number of leukocytes (21st days) and lymph decision to count lymphocytes (21st days). Results: The results that the leaf extract of purple sweet potato (ipomoea batatas L.), especially a dose of 500 mg / kg as immunomodulatory activity can increase the number of lymphocytes proliferation cell. Conclusion: Purple sweet potato leaf extract has activity against the increase in the number of lymphocytes cell especially on dose 500 mg/kg BW who induced by hepatitis B vaccine that can stimulated an immune response.